2017
DOI: 10.1038/nature22815
|View full text |Cite|
|
Sign up to set email alerts
|

T cells from patients with Parkinson’s disease recognize α-synuclein peptides

Abstract: Genetic studies associate Parkinson’s disease with alleles of the major histocompatibility complex1–3. We find that a defined set of peptides derived from α-synuclein, a protein aggregated in Parkinson’s disease4, act as antigenic epitopes displayed by these alleles and drive helper and cytotoxic T cell responses in Parkinson’s disease patients. These responses may explain the association of Parkinson’s disease with alleles of the acquired immune system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
627
4
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 648 publications
(686 citation statements)
references
References 44 publications
21
627
4
4
Order By: Relevance
“…Although the association between PD and the HLA region is complex, it has been suggested that the hits at HLA-DRB6 and HLA-DQA1 could implicate regulation of antigen presentation as a potential mechanism by which the immune response links environmental factors to genetic susceptibility in conferring risk for PD (Kannarkat et al 2015). Indeed, Sulzer et al have recently reported that α -synuclein-derived fragments act as antigenic epitopes displayed by HLA receptors, where both helper and cytotoxic T-cell responses are present in a high percentage of patients when tested (Sulzer et al 2017). …”
Section: A Glimpse Into Much Larger Networkmentioning
confidence: 99%
“…Although the association between PD and the HLA region is complex, it has been suggested that the hits at HLA-DRB6 and HLA-DQA1 could implicate regulation of antigen presentation as a potential mechanism by which the immune response links environmental factors to genetic susceptibility in conferring risk for PD (Kannarkat et al 2015). Indeed, Sulzer et al have recently reported that α -synuclein-derived fragments act as antigenic epitopes displayed by HLA receptors, where both helper and cytotoxic T-cell responses are present in a high percentage of patients when tested (Sulzer et al 2017). …”
Section: A Glimpse Into Much Larger Networkmentioning
confidence: 99%
“…Accumulated α-synuclein inside dopaminergic neurons acts as a foreign antigen that triggers a T-cell regulated response and subsequent autophagy of dopaminergic neurons (Papachroni et al 2007), which provides a possible explanation for induction of an autoimmune response. Moreover, recently it was reported that T cells from PD patients and healthy controls age-matched differentially recognize and react to certain epitopes of α-synuclein, the main protein component in Lewy Bodies (Sulzer et al, 2017). These studies indicate a role for adaptive autoimmunity in PD.…”
Section: Parkinson’s Disease and The Immune Systemmentioning
confidence: 99%
“…Lymphocyte-activation gene-3 (LAG-3), present on multiple immune cells and a ligand for human leukocyte antigen class II molecules, specifically binds to pre-fibrillary forms of α-synuclein (PFF α-synuclein), and knockout of this gene attenuates PFF α-synuclein-induced neurodegeneration (Mao et al, 2016) Based on the premises that exogenous pre-fibrillary α-synuclein can induce dopaminergic neurodegeneration (Volpicelli-Daley et al, 2011); and that PD T-cells in the CNS respond differentially to α-synuclein peptides presented by HLA (Sulzer et al, 2017), there is sufficient evidence to postulate that α-synuclein may be a link between immune dysfunction and neurodegeneration in PD. This aligns with our hypothesis that there is a potential bidirectional communication between the peripheral (immune) and central dopaminergic systems.…”
Section: Parkinson’s Disease and The Immune Systemmentioning
confidence: 99%
“…Notably, there are numerous reciprocal links between immune cell activation and alpha-synuclein aggregation. For example, alpha-synuclein fragments activate immune cells in various PD models [34], and are suggested to be one of the triggers for microglial activation in the brains of PD patients [35]. The GI tract of PD patients has elevated numbers of proinflammatory microbes, and these have been suggested to promote microglial activation and alpha-synuclein aggregation in the brain via microbial metabolites (short chain fatty acid signaling) [36].…”
Section: Editorialmentioning
confidence: 99%